Nitrogen Transfer of Two Cultivar Faba Bean (Vicia faba L.) to Oat (Avena sativa L.) - H. Purnamawati; K. Schmidtke (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2003)
Nitrogen fixed by the legume could be used by other plants, such as through rhizodeposition and direct transfer between roots. The possibility of N transfer in intercropping legum-cereal have long been observed, especially legum with short and dense root. This experiment had been carried out to determine whether there was N transfer from faba bean (Vicia faba L.) growing in association with oat (Avena sativa L.) and whether there was difference between two cultivars of faba bean in the amount of N transfer. Methods used were complete-mixed-root (CMR) between faba bean and oat, and mixed half the root of faba bean with oat (SR). As a tracer isotope 15N was used in form of K15NO3. The experiment was carried out from May 2000 through January 2001 in Institute of Agronomy and Plant Breeding, University of Goettingen Germany. The data of CMR method had great variance. Using SR method a positive value of 15N enrichment was found in oat indicated that transfer N from faba bean cv. Minica and Scirocco occurred. There was no difference found in the amount of N transferred between the two tested cultivars. Key words: N transfer, 15N, Faba bean, Oat